A review dengue incidence in Kota Bharu, Kelantan from year 1998-2003 - Narwani Hussin,; Jesni Jaafar,; Hamzah Ag Mat,; Abd Haris Muhamad,; Mohd .Noor Mamat, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Dengue is the most common and widespread arthropod borne arboviral infection in the world today. It is estimated that there are at least 100 million cases of dengue fever (DF) annually and 500,000 cases of dengue hemorrhagic fever (DHF) which require hospitalization. In Malaysia, it has become one of the major public health problems. The incidence rate of clinically diagnosed DF and DHF reported is showing an upward trend from 8.5 cases/l00,000 populations in 1988 to 88.6 cases/100, 000 populations in 2003. The objective of this analysis was to describe the incidence of dengue fever and dengue hemorrhagic fever in Kota Bharu, Kelantan from year 1998-2003. A total of 4716 dengue cases were notified involving 4476 (94.9%) DF and 240 (5.1%) DHF, which was increasing by years. The highest incidence was in January (701 or 14.9%) while the lowest was in May (188 or 4.0%). Forty percent of cases (n=1890) were in the 15-29 years old group. Majorities were Malays (4062 or 86.1%) and 2602 or 55.2% were male. A total of 4477 cases (95%) were local cases and 4289 or 91% came from urban area. For priority areas, 3772 (80%) were from priority 1. More than half of cases have positive serology result. The mean values for age, temperature, systolic and diastolic blood pressure (BP) were 27.8 + 15.4 years, 37.9 + 0.9 degree Celcius, 115 + 15.2mmHg and 73 + 11.1mmHg respectively. The mean value for time interval befween onset of symptoms and diagnosis, onset of symptoms and notification and time of diagnosis to notification were 5.1 + 2.3, 5.9 + 2.5 and 0.8 + 1.1 days respectively. All symptoms occurred in more than 96% of cases and fever was the commonest (99.7%). The incidence of dengue in Kota Bharu is comparable to that of in Malaysia. The increase in the number of cases needs to be addressed promptly with effective surveillance, prevention and control programs.